Analysis of development of gifted students in elementary school - Syam, Aldo Redho; Nurjan, Syarifan; Sumaryanti, Lilis (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aims to analyze development of gifted student’s elementary school at MI Pesantren Anak Sholeh Baitul Qur’an Gontor Ponorogo. This research uses a descriptive, qualitative approach. Data collection techniques using observation and interview techniques. Interviews were conducted with principals, teachers, guardians of students, and students. The data analysis technique was performed using an interactive model (Miles and Huberman), while the data validity test used data triangulation. The results show that the development of giftedness of student’s elementary school has been in line with the concept of the three rings of Renzulli, where the characteristics of gifted students at MI Pesantren Anak Sholeh Baitul Qur’an Gontor, including showing above-average ability, show commitment to the task. as enthusiasm, and involvement with a particular problem or area, self-confidence and desire, showing high creativity as fluency, flexibility, and authenticity in thinking, openness to experience, curiosity, and the courage to take steps.